The Composition of Public Expenditure, Physical Infrastructure and Economic Growth in Nepal - Shrestha, Prakash Kumar (NRB Economic Review, 2009)
This paper investigates the role of composition of public expenditure, particularly the expenditure on physical infrastructure, on economic growth in Nepal from the time series perspective based on the endogenous growth model. The impact of public expenditure on economic growth has been found to be positive. Hence, low economic growth in Nepal in recent years can be attributed to low government expenditure on infrastructure. Availability of infrastructure situation is very dismal. Given the sustainable debt scenario, Nepal can go for more investment in infrastructure by external borrowing at least for the medium term.